Identification of Novel Genes Involved in Sarcopenia Through RNAi Screening in Caenorhabditis elegans - Kashyap, Luv (Oxford University Press, 2012)
BACKGROUND. Aging in humans is characterized by a progressive loss of muscle mass and strength known as sarcopenia. Although considered to be a normal aspect of aging, the loss of strength can have significant effects on the health, functioning, and independence of elderly individuals. Although these aspects of sarcopenia have been well studied, the molecular mechanisms leading to its development are still unclear. The nematode Caenorhabditis elegans might be a novel animal model for sarcopenia as worms experience sarcopenia during aging and mutations affecting the daf-2/insulin-like signaling pathway are able to delay this process. METHODS. Via the use of RNA interference, we screened a total of 43 genes, most of which have been shown to be required for the enhanced longevity of daf-2 mutants, to assess for the effects of these genes on muscle function and worm mobility during aging. RESULTS. We identified 17 novel genes that are essential for the delay in the onset of sarcopenia in daf-2 mutants. The identified genes include splicing factors, vacuolar sorting proteins, transcription factors, and metabolic enzymes. Using a transgenic strain that only responds to RNA interference in the body wall muscle, we also found that most of the identified genes act in muscle to prevent the onset of sarcopenia. CONCLUSIONS. Our results demonstrate that at least in worms, specific genetic pathways that modify the development of sarcopenia can be identified. Interestingly, almost all the identified genes also have a known human homolog, and hence, our findings may offer significant leads toward the identification of genes involved in sarcopenia in people.